Advances in Large-Scale Metrology – Review and future trends. Issue 2 (2016) - Schmitt, R.H.; Peterek, M.; Morse, E.; Knapp, W.; Galetto, M.; Härtig, F.; Goch, G.; Hughes, B.; Forbes, A.; Estler, W.T.
Abstract: The field of Large-Scale Metrology has been studied extensively for many decades and represents the combination and competition of topics as diverse as geodesy and laboratory calibration. A primary reason that Large-Scale Metrology continues to represent the research frontier is that technological advances introduced and perfected at a conventional scale face additional challenges which increase non-linearly with size. This necessitates new ways of considering the entire measuring process, resulting in the application of concepts such as virtual measuring processes and cyber-physical systems. This paper reports on the continuing evolution of Large-Scale Metrology.